Exploring multisensory in enhancing literacy of dyslexic students - Kunasegran, Kavenia; Subramaniam, Vijayaletchumy (Human Resources Management Academic Research Society (HRMARS), 2024)
This study focuses on the multisensory learning approach in the literacy mastery of dyslexic students. The objective of this study is to identify reading problems according to the LINUS literacy construct and explain reading errors according to Levinson's Theory (1994) among dyslexic students. Next, the researcher will apply the multisensory learning approach to overcome the problem and analyze the effectiveness of the multisensory learning approach in the reading literacy aspect of dyslexic students. The researcher used the A-B-A research design to determine the effectiveness of multisensory learning in literacy mastery of dyslexic students through three phases, namely baseline (A), intervention (B), and maintenance (C). In explaining reading errors among dyslexic students, the researcher used the Levinson Theory of Dyslexia (1994). The Orton-Gillingham approach (1948) and the Structured Literacy approach (2004) are used in the application of multisensory learning. The Phonological Theory of Dyslexia Deficit (1999) is used in analyzing the effectiveness of multisensory in dyslexic students' mastery of literacy. The researcher chose the Malaysian Dyslexia Center (Ampang) as the study location. This study involved a total of 10 dyslexic students as study subjects and 15 dyslexic teachers as study respondents. The researcher has used observation, interview, and survey methods. The researcher used the LINUS Literacy Reading Diagnostic Test, Malay language Level 1 reading texts, Multisensory Dys-Literacy Kit and questionnaires as research tools. The findings of this study prove that the study subjects have reading problems according to the LINUS construct which evaluates 12 reading skills. The researcher found that dyslexic students have not mastered the language's phonemic, phonetic, and phonological aspects. The researcher also found some research findings beyond the expectations of Levinson's Theory (1994). The results of this study found that the influence of English phonics reading also affects dyslexic students' reading skills in Malay. In the final phase of this study, the researcher analyzed the effectiveness of the multisensory learning approach and has proven a significant improvement in the literacy skills of dyslexic students.